Prevalence of Anemia among Older Adults Residing in the Coastal and Andes Mountains in Ecuador: Results of the SABE Survey. (21st February 2017) - Orces, Carlos H.
Abstract : Objectives . To estimate the prevalence of anemia and its determinants among older adults in Ecuador. Methods . The present study was based on data from the National Survey of Health, Wellbeing, and Aging. Hemoglobin concentrations were adjusted by participants' smoking status and altitude of residence, and anemia was defined according to the World Health Organization criteria (<12 g/dL in women and <13 g/dL in men). Gender-specific logistic regression models were used to examine the association between demographic and health characteristics and anemia. Results . A total of 2, 372 subjects with a mean age of 71.8 (SD 8.2) years had their hemoglobin measured, representing an estimated 1.1 million older adults. The crude prevalence of anemia was 20.0% in women and 25.2% in men. However, higher anemia prevalence rates were seen with advancing age among black women and subjects residing in the urban coast. Likewise, certain health conditions such as hypoalbuminemia, cancer in men, chronic kidney disease, iron deficiency, and low grade inflammation were associated with increased odds of having anemia. Conclusions . Anemia is a prevalent condition among older adults in Ecuador. Moreover, further research is needed to examine the association between anemia and adverse health-related outcomes among older Ecuadorians.